The Impact of Corporate Sustainability on Profitability and Risk in Companies Listed on the Lima Stock Exchange, Peru, 2022: A Segmented Analysis Based on ESG Pillars - Mendiola-Contreras, Luis (2023)
In recent decades, the convergence between environmental sustainability and financial performance has drawn considerable interest within the corporate sphere. This study delves into the relationship between ESG scores and the profitability (ROA) of companies listed on the Lima Stock Exchange (BVL), revealing significant patterns that underscore the strategic value of robust ESG management. The findings indicate that companies with high ESG scores, particularly in the environmental pillar, achieve higher profitability and exhibit reduced volatility, suggesting greater financial stability and lower perceived risk by investors. Environmental practices emerge as a key factor in beta reduction, while social and governance practices, although trending toward reduced volatility, do not show a statistically significant relationship. These insights reinforce previous research in Latin America and emphasize the importance of adopting sustainable strategies not only to enhance corporate responsibility but also to strengthen market competitiveness and profitability. This study invites reflection on the role of ESG in creating value and building a sustainable competitive advantage for companies in emerging economies.